Supported three-way catalyst as well as preparation method and application thereof
By using perovskite-type high-temperature thermoelectric materials as support in the three-way catalyst, combined with the thermoelectric effect, and loading the Pt/Ce0.8Zr0.2O2/Al2O3 catalyst, the problem of low catalytic efficiency of the existing three-way catalyst is solved, and a more efficient automobile exhaust purification effect is achieved.
Patent Information
- Application Number
- CN202510049846.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-05-02
AI Technical Summary
The existing three-way catalyst has low catalytic efficiency and is difficult to effectively purify harmful gases in automobile exhaust.
Perovskite high-temperature thermoelectric material is used as a porous support and is loaded with Pt/Ce0.8Zr0.2O2/Al2O3 catalyst to improve the activity of the catalyst through the thermoelectric effect and enhance the purification effect of automobile exhaust.
The thermoelectric effect promotes carrier migration and diffusion, improves the catalytic activity of the catalyst, improves the purification efficiency of NO, CO and hydrocarbons, reduces the amount of precious metals, and reduces the cost of manufacturing and replacement.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the field of thermoelectric catalysis and relates to a supported three-way catalyst and a preparation method and application thereof. Background Art
[0002] Three-way catalysis refers to the process of converting harmful gases such as CO, NO and hydrocarbons emitted from automobile exhaust into harmless CO2, N2 and H2O through oxidation and reduction, which is achieved by covering the porous carrier of the three-way catalytic converter with a three-way catalyst coating. Most of the existing three-way catalysts are composed of cerium, zirconium, aluminum oxide and precious metal catalysts such as platinum, rhodium and palladium. Among them, cerium, zirconium and other components are mainly used to form an oxygen storage active layer, aluminum oxide is used for surface modification of the catalyst carrier to increase the specific surface area of the catalyst carrier and the adhesion ratio of the catalyst, and precious metals such as platinum, rhodium and palladium are used as catalytic active components. The porous carrier is mainly porous ceramics and metals, such as cordierite, mullite, copper and aluminum, which have the characteristics of low thermal expansion coefficient, good thermal stability and high mechanical strength. However, both ceramic and metal carriers mainly play a structural support role and provide sufficient adhesion surface area for the catalyst coating. They do not have catalytic activity themselves and cannot promote the three-way catalytic process. Summary of the invention
[0003] The purpose of the present invention is to address the problem of low catalytic efficiency of some three-way catalysts, propose a supported three-way catalyst and its preparation method and application, and use perovskite-type high-temperature thermoelectric material as a porous carrier, which can effectively improve the purification effect of the three-way catalyst on automobile exhaust through the thermoelectric effect of the matrix.
[0004] The present invention is achieved through the following technical solutions: A supported three-way catalyst comprising La x Sr (1-x) Nb y Ti (1-y) O3 porous carrier and loaded on La x Sr (1-x) Nb y Ti (1-y) Pt / Ce on O3 porous support 0.8 Zr 0.2 O2 / Al2O3 catalyst, wherein x is 0.05~0.2 and y is 0.05~0.2.
[0005] The method for preparing the supported three-way catalyst of the present invention comprises: S1, Synthesis of La by solid phase sintering x Sr (1-x) Nb y Ti (1-y) O3 powder; S2, prepared La x Sr (1-x) Nb y Ti (1-y) O3 powder is used as raw material and La is prepared by 3D printing technology x Sr (1-x) Nb y Ti (1-y) O3 porous carrier; S3, mixing Ce(NO3)3 solution, ZrO(NO3)2 solution and γ-Al2O3 powder, heating them in air, and then drying them; calcining the dried powder, cooling it, and grinding it to obtain a mixed oxide powder; S4, adding the mixed oxide powder to the Pt(NO2)2(NH3)2 solution to form an impregnation slurry; S5, using impregnation slurry to La x Sr (1-x) Nb y Ti (1-y) The O3 porous carrier is impregnated, then dried and calcined to obtain a supported three-way catalyst.
[0006] Preferably, S1 specifically comprises: mixing strontium carbonate, titanium dioxide, lanthanum oxide and niobium pentoxide, grinding and pre-calcining; grinding the pre-calcined powder, burying and burning with charcoal powder under an argon atmosphere, and grinding to obtain La x Sr (1-x) Nb y Ti (1-y) O3 powder.
[0007] Preferably, S2 specifically comprises: La x Sr (1-x) Nb y Ti (1-y) O3 powder is mixed with photosensitive resin, dispersant is added, ball milled, defoamed, cured by DLP 3D printing, degreased and decarbonized, and then sintered to obtain La x Sr (1-x) Nb y Ti (1-y) O3 porous carrier.
[0008] Furthermore, the sintering temperature in S2 is 1300~1400°C, and the time is 4~6h.
[0009] Preferably, in S3, the heating temperature is 100-120°C, and the time is 10-14 hours; the calcination temperature is 900-1100°C, and the time is 2-4 hours.
[0010] Preferably, in S4, the concentration of the Pt (NO2)2(NH3)2 solution is 1wt%~10wt%.
[0011] Preferably, in S5, the calcination temperature is 900-1100° C. and the time is 2-4 hours.
[0012] The invention also provides application of the supported three-way catalyst in automobile exhaust treatment.
[0013] The present invention also provides a three-way catalytic converter, which includes the supported three-way catalyst as described above.
[0014] Compared with the prior art, the present invention has the following beneficial effects: The present invention adopts doped SrTiO3 porous thermoelectric carrier (La x Sr (1-x) Nb y Ti (1-y) O3) as a three-way catalyst Pt / Ce 0.8 Zr 0.2 O2 / Al2O3 porous support, Pt / Ce 0.8 Zr 0.2 The O2 / Al2O3 catalyst involves the adsorption and desorption of pollutants such as CO, NO, and HC on the catalyst surface during the three-way catalytic process. The redox reaction in the adhesion layer is accompanied by the migration and diffusion of electrons, and the migration and diffusion rates affect the catalytic activity of the catalyst. Figure 7 As shown, the heat from the high-temperature exhaust gas discharged from the engine makes La x Sr (1-x) Nb y Ti (1-y) Two temperature gradients are formed in O3, from the end close to the engine to the end close to the air, and from the end close to the porous inner wall to the end far away from the porous inner wall, which leads to the directional migration of carriers; La x Sr (1-x) Nb y Ti (1-y) O3 is anisotropic, and will generate a thermoelectric field E perpendicular to the porous inner wall through the longitudinal thermoelectric effect and the transverse thermoelectric effect. ⊥ and the thermoelectric field E parallel to the porous inner wall ∥ , is Pt / Ce 0.8 Zr 0.2 O2 / Al2O3 catalysts provide additional active carriers, Pt / Ce 0.8 Zr 0.2 The catalytic active sites of O2 / Al2O3 will receive active carriers generated by the thermoelectric effect. ∥ and E ⊥Under the action of, the transfer of carriers in the catalytic active sites is promoted, thereby improving the catalytic activity of the three-way catalyst, and then improving the purification efficiency of NO, CO and hydrocarbons during exhaust emissions. At the same time, the present invention performs element doping on strontium titanate to increase the carrier concentration in strontium titanate, thereby optimizing the thermoelectric properties of strontium titanate, and then improving the effect of thermoelectric effect in promoting three-way catalysis. Based on the promotion of three-way catalysis by thermoelectric effect, the present invention can reduce the amount of precious metals such as Pt and reduce the manufacturing and replacement costs of three-way catalytic converters while meeting automobile exhaust emission standards. The catalyst of the present invention has the characteristics of low cost, good thermal stability, excellent high-temperature antioxidant performance, etc., and can still maintain good performance above 1100K.
[0015] The preparation method of the supported three-way catalyst of the present invention adopts a solid phase sintering method to prepare La x Sr (1-x) Nb y Ti (1-y) O3 powder, and then use 3D printing to prepare a porous carrier, and then load Pt / Ce by impregnation 0.8 Zr 0.2 O2 / Al2O3 catalyst. The porous carrier is prepared by 3D printing, which can accurately control the pore shape, pore size and size of the carrier, with high production efficiency and low environmental pollution.
[0016] Furthermore, the solid phase reaction of strontium titanate is prone to incomplete reaction due to uneven reactants and insufficient contact. The pre-firing and then sintering of the present invention can ensure that the reaction is complete. The buried firing isolates oxygen, which can form a large number of oxygen vacancies in the fired strontium titanate to improve the electrical properties. Charcoal powder can prevent oxidation. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0018] Figure 1 is La of Example 2 0.1 Sr 0.9 Nb 0.1 Ti 0.9 SEM morphology of O3 powder.
[0019] Figure 2 is La of Example 2 0.1 Sr 0.9 Nb 0.1 Ti 0.9 XRD spectrum of O3 powder.
[0020] Figure 3 (a) and (b) are La made by 3D printing. 0.1 Sr 0.9 Nb 0.1 Ti 0.9 Cross-sectional view of O3 porous thermoelectric carrier and cross-sectional view of purchased commercial mullite porous carrier.
[0021] Figure 4 (a) and (b) are respectively the conversion rate curve of the catalyst prepared in Example 1 and the purification curve of the polluted gas (C: initial concentration of the polluted gas, C1: concentration of the polluted gas after catalytic purification).
[0022] Figure 5 (a) and (b) are respectively the conversion rate curve of the catalyst prepared in Example 2 and the purification curve of the polluted gas (C: initial concentration of the polluted gas, C1: concentration of the polluted gas after catalytic purification).
[0023] Figure 6 (a) and (b) are respectively the conversion rate curve of the catalyst prepared in Comparative Example 1 and the purification curve of the polluted gas (C: initial concentration of the polluted gas, C1: concentration of the polluted gas after catalytic purification).
[0024] Figure 7 It is the thermoelectric field principle diagram of the catalyst of the present invention. DETAILED DESCRIPTION
[0025] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0026] It should be noted that the process equipment or devices not specifically specified in the following embodiments are all conventional equipment or devices in the art.
[0027] It should be noted that the terms "include" and "have" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or to define the scope of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the present invention without substantially changing the technical content.
[0028] The supported three-way catalyst of the present invention comprises La x Sr (1-x) Nb y Ti (1-y) O3 porous carrier and loaded on La x Sr (1-x) Nb y Ti (1-y) Pt / Ce on O3 porous support 0.8 Zr 0.2 O2 / Al2O3 catalyst, wherein x is 0.05~0.2 and y is 0.05~0.2.
[0029] The method for preparing the supported three-way catalyst of the present invention comprises: S1, Synthesis of La by solid phase sintering x Sr (1-x) Nb y Ti (1-y) O3 powder; S2, prepared La x Sr (1-x) Nb y Ti (1-y) O3 powder is used as raw material and La is prepared by 3D printing technology x Sr (1-x) Nb y Ti (1-y) O3 porous carrier; S3, mixing Ce(NO3)3 solution, ZrO(NO3)2 solution and γ-Al2O3 powder, heating them in air, and then drying them; calcining the dried powder, cooling it, and grinding it to obtain a mixed oxide powder; S4, adding the mixed oxide powder to the Pt(NO2)2(NH3)2 solution to form an impregnation slurry; S5, using impregnation slurry to La x Sr (1-x) Nb yTi (1-y) The O3 porous carrier is impregnated, then dried and calcined to obtain a supported three-way catalyst.
[0030] In some specific embodiments of the present invention, S1 specifically comprises: mixing strontium carbonate, titanium dioxide, lanthanum oxide and niobium pentoxide, grinding and pre-calcining; grinding the pre-calcined powder, burning it with charcoal powder under an argon atmosphere, and grinding it to obtain La x Sr (1-x) Nb y Ti (1-y) O3 powder; pre-firing temperature is 1200~1300℃, time is 5~7h; burial temperature is 1200~1400℃, time is 5~7h.
[0031] In some specific embodiments of the present invention, S2 specifically includes: La x Sr (1-x) Nb y Ti (1-y) O3 powder is mixed with photosensitive resin, dispersant is added, ball milled, defoamed, cured by DLP 3D printing, degreased and decarbonized, and then sintered to obtain La x Sr (1-x) Nb y Ti (1-y) O3 porous carrier; Among them, La x Sr (1-x) Nb y Ti (1-y) The mass of O3 powder accounts for 2.3% of photosensitive resin and La x Sr (1-x) Nb y Ti (1-y) O3 powder and dispersant account for 60%~80% of the total mass; the photosensitive resin is preferably YF-RC2110005, the main components of which are polyurethane acrylate (PUA), acrylate (ACM), diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide (TPO) and 4-acryloyl morpholine (ACMO); the dispersant is preferably carboxymethyl cellulose (CMC), the addition amount is preferably 3%, and the ball-to-material mass ratio is preferably 1:1. The degreasing temperature is 550~650℃, the heating rate is 3~5℃ / min; the decarburization temperature is 750~850℃, the holding time is 2~4h, the heating rate is 3~5℃ / min; the sintering temperature is 1300~1400℃, the holding time is 4~6h, and the heating rate is 2~4℃ / min.
[0032] In the present invention S3, γ-Al2O3 is used as a carrier and Ce is loaded by an impregnation method. 0.8 Zr 0.2O2, to obtain a mixed oxide powder; wherein the heating temperature is 100 ~ 120 ° C, the time is 10 ~ 14h; the calcination temperature is 900 ~ 1100 ° C, the time is 900 ~ 1100h.
[0033] In some specific embodiments of the present invention, the concentration of the Pt (NO2)2(NH3)2 solution is 1wt%~10wt%.
[0034] In S5 of the present invention, La x Sr (1-x) Nb y Ti (1-y) O3 porous carrier is used as carrier, and Pt / Ce is loaded by impregnation method. 0.8 Zr 0.2 O2 / Al2O3, among which Pt / Ce 0.8 Zr 0.2 The O2 / Al2O3 loading is 5wt%~20wt%; the calcination temperature is 900~1100℃, and the time is 900~1100h.
[0035] The supported three-way catalyst of the present invention can be used for automobile exhaust treatment, using high-temperature exhaust as a heat source to generate a thermoelectric effect, thereby improving the catalytic efficiency of the three-way catalyst, while adjusting the carrier concentration of strontium titanate by element doping, thereby enhancing the promoting effect on the three-way catalysis.
[0036] Example 1 Step 1: Preparation of La 0.1 Sr 0.9 Nb 0.1 Ti 0.9 O3 powder (1) Lanthanum oxide La2O3 and niobium pentoxide Nb2O5 were selected as doping sources. Strontium carbonate, titanium dioxide, lanthanum oxide and niobium pentoxide were mixed in a molar ratio of 0.9:0.9:0.05:0.05, ground for 2 h, and pre-fired in a muffle furnace at a pre-fired temperature of 1250 ° C for 6 h. (2) The pre-calcined powder was ground for 1 hour and then burned in a tube furnace under an argon atmosphere at 1300°C for 6 hours to obtain La 0.1 Sr 0.9 Nb 0.1 Ti 0.9 O3.
[0037] Step 2: Preparation of La 0.1 Sr 0.9 Nb 0.1 Ti 0.9 O3 porous carrier (1) Prepare La x Sr (1-x) Nby Ti (1-y) O3 powder was mixed with photosensitive resin YF-RC2110005, and dispersant carboxymethyl cellulose (CMC) was added. All materials were added into a ball mill and ball milled for 2 hours. 0.1 Sr 0.9 Nb 0.1 Ti 0.9 O3 powder and dispersant total mass, La 0.1 Sr 0.9 Nb 0.1 Ti 0.9 The amount of O3 powder added is 75wt%, and the amount of dispersant added is 3wt%; (2) The milled slurry is passed through a 10-mesh sieve and defoamed in a vacuum drying oven; (3) Place the defoamed slurry into the 3D printer tank for DLP 3D printing to obtain La 0.1 Sr 0.9 Nb 0.1 Ti 0.9 O3 porous carrier embryo, including 6 layers of DLP substrate, substrate curing time of 35s, printing layer thickness of 20μm, and main body curing time of 5s; (4) La obtained by 3D printing 0.1 Sr 0.9 Nb 0.1 Ti 0.9 The O3 porous carrier embryo was placed in a tube furnace for degreasing, and the heating rate was 4°C / min in an argon atmosphere, and the maximum temperature was 600°C; (5) La after degreasing 0.1 Sr 0.9 Nb 0.1 Ti 0.9 The O3 porous carrier embryo was placed in a muffle furnace for decarburization, with a heating rate of 4°C / min, a maximum temperature of 800°C, and a holding time of 3h; (6) The decarburized La 0.1 Sr 0.9 Nb 0.1 Ti 0.9 The O3 porous carrier embryo was placed in a muffle furnace for sintering at a temperature of 1350°C, a heating rate of 3°C, and a holding time of 5h to obtain La 0.1 Sr 0.9 Nb 0.1 Ti 0.9 O3 porous carrier.
[0038] Step 3: Pt / Ce 0.8 Zr 0.2 Synthesis and coating of O2 / Al2O3 catalysts (1) Ce(NO3)3 solution, ZrO(NO3)2 solution and γ-Al2O3 powder were mixed in a molar ratio of 0.24:0.06:1, stirred in air for 1 h, heated in air at 110 °C for 12 h, and dried; (2) Place the dried powder into a muffle furnace, treat at 1000°C for 3 h, and grind for 2 h after cooling; (3) The ground mixed oxide powder was added to a 1 wt% Pt(NO2)2(NH3)2 solution to form an impregnation slurry. 0.1 Sr 0.9 Nb 0.1 Ti 0.9 The O3 porous support was immersed in the impregnation slurry for 6 h, stirred in air for 1 h, heated in air at 110 °C for 12 h, and dried; (4) The dried La 0.1 Sr 0.9 Nb 0.1 Ti 0.9 The O3 porous carrier was placed in a muffle furnace and treated at 1000°C for 3 h to obtain a Pt / Ce coated 0.8 Zr 0.2 La over O2 / Al2O3 catalysts 0.1 Sr 0.9 Nb 0.1 Ti 0.9 O3 porous carrier.
[0039] Example 2 Step 1: Preparation of La 0.1 Sr 0.9 Nb 0.1 Ti 0.9 O3 powder (1) Lanthanum oxide La2O3 and niobium pentoxide Nb2O5 were selected as doping sources. Strontium carbonate, titanium dioxide, lanthanum oxide and niobium pentoxide were mixed in a molar ratio of 0.9:0.9:0.05:0.05, ground for 2 h, and pre-fired in a muffle furnace at a pre-fired temperature of 1250 ° C for 6 h. (2) The pre-calcined powder was ground for 1 hour and then burned in a tube furnace under an argon atmosphere at 1300°C for 6 hours to obtain La 0.1 Sr 0.9 Nb 0.1 Ti 0.9 O3.
[0040] Step 2: Preparation of La 0.1 Sr 0.9 Nb 0.1 Ti 0.9 O3 porous carrier (1) Prepare La0.1 Sr 0.9 Nb 0.1 Ti 0.9 O3 powder was mixed with photosensitive resin YF-RC2110005, and dispersant carboxymethyl cellulose (CMC) was added. All materials were added into a ball mill and ball milled for 2 hours. 0.1 Sr 0.9 Nb 0.1 Ti 0.9 O3 powder and dispersant total mass, La 0.1 Sr 0.9 Nb 0.1 Ti 0.9 The amount of powder added is 75wt%, and the amount of dispersant added is 3wt%; (2) The milled slurry is passed through a 10-mesh sieve and defoamed in a vacuum drying oven; (3) Place the defoamed slurry into the 3D printer tank for DLP 3D printing to obtain La 0.1 Sr 0.9 Nb 0.1 Ti 0.9 O3 porous carrier embryo, including 6 layers of DLP substrate, substrate curing time of 35s, printing layer thickness of 20μm, and main body curing time of 5s; (4) La obtained by 3D printing 0.1 Sr 0.9 Nb 0.1 Ti 0.9 The O3 porous carrier embryo was placed in a tube furnace for degreasing, and the heating rate was 4°C / min in an argon atmosphere, and the maximum temperature was 600°C; (5) La after degreasing 0.1 Sr 0.9 Nb 0.1 Ti 0.9 The O3 porous carrier embryo was placed in a muffle furnace for decarburization, with a heating rate of 4°C / min, a maximum temperature of 800°C, and a holding time of 3h; (6) The decarburized La 0.1 Sr 0.9 Nb 0.1 Ti 0.9 The O3 porous carrier embryo was placed in a muffle furnace for sintering at a temperature of 1350°C, a heating rate of 3°C, and a holding time of 5h to obtain La 0.1 Sr 0.9 Nb 0.1 Ti 0.9 O3 porous carrier.
[0041] Step 3: Pt / Ce 0.8 Zr 0.2 Synthesis and coating of O2 / Al2O3 catalysts (1) Ce(NO3)3 solution, ZrO(NO3)2 solution and γ-Al2O3 powder were mixed in a molar ratio of 0.24:0.06:1, stirred in air for 1 h, heated in air at 110 °C for 12 h, and dried; (2) Place the dried powder into a muffle furnace, treat at 1000°C for 3 h, and grind for 2 h after cooling; (3) The ground mixed oxide powder was added to a 5 wt% Pt(NO2)2(NH3)2 solution to form an impregnation slurry. 0.1 Sr 0.9 Nb 0.1 Ti 0.9 The O3 porous support was immersed in the impregnation slurry for 6 h, stirred in air for 1 h, heated in air at 110 °C for 12 h, and dried; (4) The dried La 0.1 Sr 0.9 Nb 0.1 Ti 0.9 The O3 porous carrier was placed in a muffle furnace and treated at 1000°C for 3 h to obtain a Pt / Ce coated 0.8 Zr 0.2 La over O2 / Al2O3 catalysts 0.1 Sr 0.9 Nb 0.1 Ti 0.9 O3 porous carrier.
[0042] Example 3 Step 1: Preparation of La 0.1 Sr 0.9 Nb 0.1 Ti 0.9 O3 powder (1) Lanthanum oxide La2O3 and niobium pentoxide Nb2O5 were selected as doping sources. Strontium carbonate, titanium dioxide, lanthanum oxide and niobium pentoxide were mixed in a molar ratio of 0.9:0.9:0.05:0.05, ground for 2 h, and pre-fired in a muffle furnace at a pre-fired temperature of 1250 ° C for 6 h. (2) The pre-calcined powder was ground for 1 hour and then burned in a tube furnace under an argon atmosphere at 1300°C for 6 hours to obtain La 0.1 Sr 0.9 Nb 0.1 Ti 0.9 O3.
[0043] Step 2: Preparation of La 0.1 Sr 0.9 Nb 0.1 Ti 0.9 O3 porous carrier (1) Prepare La 0.1 Sr 0.9 Nb 0.1 Ti 0.9 O3 powder was mixed with photosensitive resin YF-RC2110005, and dispersant carboxymethyl cellulose (CMC) was added. All materials were added into a ball mill and ball milled for 2 hours. 0.1 Sr 0.9 Nb 0.1 Ti 0.9 O3 powder and dispersant total mass, La 0.1 Sr 0.9 Nb 0.1 Ti 0.9 The amount of O3 powder added is 75wt%, and the amount of dispersant added is 3wt%; (2) The milled slurry is passed through a 10-mesh sieve and defoamed in a vacuum drying oven; (3) Place the defoamed slurry into the 3D printer tank for DLP 3D printing to obtain La 0.1 Sr 0.9 Nb 0.1 Ti 0.9 O3 porous carrier embryo, including 6 layers of DLP substrate, substrate curing time of 35s, printing layer thickness of 20μm, and main body curing time of 5s; (4) La obtained by 3D printing 0.1 Sr 0.9 Nb 0.1 Ti 0.9 The O3 porous carrier embryo was placed in a tube furnace for degreasing, and the heating rate was 4°C / min in an argon atmosphere, and the maximum temperature was 600°C; (5) La 0.1 Sr 0.9 Nb 0.1 Ti 0.9 The O3 porous carrier embryo was placed in a muffle furnace for decarburization, with a heating rate of 4°C / min, a maximum temperature of 800°C, and a holding time of 3h; (6) The decarburized La 0.1 Sr 0.9 Nb 0.1 Ti 0.9 The O3 porous carrier embryo was placed in a muffle furnace for sintering at a temperature of 1350°C, a heating rate of 3°C, and a holding time of 5h to obtain La 0.1 Sr 0.9 Nb 0.1 Ti 0.9 O3 porous carrier.
[0044] Step 3: Pt / Ce 0.8 Zr 0.2Synthesis and coating of O2 / Al2O3 catalysts (1) Ce(NO3)3 solution, ZrO(NO3)2 solution and γ-Al2O3 powder were mixed in a molar ratio of 0.24:0.06:1, stirred in air for 1 h, heated in air at 110 °C for 12 h, and dried; (2) Place the dried powder into a muffle furnace, treat at 1000°C for 3 h, and grind for 2 h after cooling; (3) The ground mixed oxide powder was added to a 10 wt% Pt(NO2)2(NH3)2 solution to form an impregnation slurry. 0.1 Sr 0.9 Nb 0.1 Ti 0.9 The O3 porous support was immersed in the impregnation slurry for 6 h, stirred in air for 1 h, heated in air at 110 °C for 12 h, and dried; (4) The dried La 0.1 Sr 0.9 Nb 0.1 Ti 0.9 The O3 porous carrier was placed in a muffle furnace and treated at 1000°C for 3 h to obtain a Pt / Ce coated 0.8 Zr 0.2 La over O2 / Al2O3 catalysts 0.1 Sr 0.9 Nb 0.1 Ti 0.9 O3 porous carrier.
[0045] Comparative Example 1 In this experiment, commercial mullite honeycomb ceramics purchased were used as the porous carrier, and compared with Example 2.
[0046] Step 1: Pt / Ce 0.8 Zr 0.2 Synthesis and coating of O2 / Al2O3 catalysts (1) Ce(NO3)3 solution, ZrO(NO3)2 solution and γ-Al2O3 powder were mixed in a molar ratio of 0.24:0.06:1, stirred in air for 1 h, heated in air at 110 °C for 12 h, and dried; (2) Place the dried powder into a muffle furnace, treat at 1000°C for 3 h, and grind for 2 h after cooling; (3) adding the ground mixed oxide powder to a 5 wt % Pt(NO2)2(NH3)2 solution to form an impregnation slurry, placing the mullite porous support in the impregnation slurry for 6 h, stirring in air for 1 h, heating in air at 110 °C for 12 h, and drying; (4) The dried mullite porous carrier was placed in a muffle furnace and treated at 1000°C for 3 h to obtain a Pt / Ce coated 0.8 Zr 0.2 Mullite porous support for O2 / Al2O3 catalyst.
[0047] The La prepared in Example 2 0.1 Sr 0.9 Nb 0.1 Ti 0.9 The morphology and phase of O3 powder were characterized. Figure 1 is La of Example 2 0.1 Sr 0.9 Nb 0.1 Ti 0.9 The SEM morphology of O3 powder shows that the sample powder is in the form of particles with relatively uniform size. 0.1 Sr 0.9 Nb 0.1 Ti 0.9 O3 powder was subjected to XRD phase analysis, such as Figure 2 As shown, its physical phase is cubic SrTiO3 crystal type. Figure 3 (a) is La made by DLP 3D printing 0.1 Sr 0.9 Nb 0.1 Ti 0.9 The cross-section of the O3 porous carrier is as follows: Figure 3 As shown in (b), both exhibit a porous morphology with relatively uniform pore size and pore position.
[0048] The Pt / Ce coated 0.8 Zr 0.2 La over O2 / Al2O3 catalysts 0.1 Sr 0.9 Nb 0.1 Ti 0.9 The catalytic activity of the porous carrier was tested. The simulated gas composition used in the experiment was: 0.12% CO, 0.11% NO, 0.1% O2, 0.05% C3H6, 15% CO2, and N2 was used as the balance. The curves of the conversion rate of the catalyst in Example 1 and Example 2 with temperature are shown in Figures 1 and 2. Figure 4 and Figure 5 shown. Figure 5 In Example 2, Pt / Ce 0.8 Zr 0.2 O2 / Al2O3 catalyst showed excellent catalytic activity for NO, CO and C3H6. The conversion rate of the three gases can reach more than 90% at around 600℃. Figure 4 and Figure 5 In Example 1, a Pt(NO2)2(NH3)2 solution with a lower concentration was used for impregnation. The catalytic activity of the catalyst decreased, but due to the promotion of the thermoelectric effect on the three-way catalysis, it can still show a high conversion rate for the three gases at around 650°C. Among them, the reduction in Pt content has a greater impact on the catalysis of CO and NO, while the conversion rate of HC does not change much. Figure 6 (a) and (b) are the conversion rate curve of the catalyst prepared in Comparative Example 1 and the purification curve of polluted gas, respectively. Figure 5 and Figure 6 , La 0.1 Sr 0.9 Nb 0.1 Ti 0.9 The catalytic curves of the catalysts supported by the O3 porous carrier and the mullite carrier are close at low temperatures, but at high temperatures, the La 0.1 Sr 0.9 Nb 0.1 Ti 0.9 The catalyst supported by the O3 porous carrier has a better catalytic effect on NO. The reason for this result is that La 0.1 Sr 0.9 Nb 0.1 Ti 0.9 O3 is a high-temperature thermoelectric material. Its thermoelectric performance is poor at low temperatures. As the temperature rises, its thermoelectric performance gradually improves, and its catalytic promotion effect becomes more significant. In summary, it is completely feasible for the present invention to promote three-way catalysis based on the thermoelectric effect.
Claims
1. A supported three-way catalyst, characterized in that: Including La x Sr (1-x) Nb y Ti (1-y) O3 porous carrier and loaded on La x Sr (1-x) Nb y Ti (1-y) Pt / Ce on O3 porous support 0.8 Zr 0.2 O2 / Al2O3 catalyst, wherein x is 0.05~0.2 and y is 0.05~0.
2.
2. The method for preparing the supported three-way catalyst according to claim 1, characterized in that: include: S1, Synthesis of La by solid phase sintering x Sr (1-x) Nb y Ti (1-y) O3 powder; S2, prepared La x Sr (1-x) Nb y Ti (1-y) O3 powder is used as raw material and La is prepared by 3D printing technology x Sr (1-x) Nb y Ti (1-y) O3 porous carrier; S3, mixing Ce(NO3)3 solution, ZrO(NO3)2 solution and γ-Al2O3 powder, heating them in air, and then drying them; calcining the dried powder, cooling it, and grinding it to obtain a mixed oxide powder; S4, adding the mixed oxide powder to the Pt(NO2)2(NH3)2 solution to form an impregnation slurry; S5, using impregnation slurry to La x Sr (1-x) Nb y Ti (1-y) The O3 porous carrier is impregnated, then dried and calcined to obtain a supported three-way catalyst.
3. The method for preparing a supported three-way catalyst according to claim 2, characterized in that: S1 specifically comprises: mixing strontium carbonate, titanium dioxide, lanthanum oxide and niobium pentoxide, grinding and pre-calcining; grinding the pre-calcined powder, burying and burning with charcoal powder under an argon atmosphere, and grinding to obtain La x Sr (1-x) Nb y Ti (1-y) O3 powder.
4. The method for preparing a supported three-way catalyst according to claim 2, characterized in that: S2 specifically includes: x Sr (1-x) Nb y Ti (1-y) O3 powder is mixed with photosensitive resin, dispersant is added, ball milled, defoamed, cured by DLP 3D printing, degreased and decarbonized, and then sintered to obtain La x Sr (1-x) Nb y Ti (1-y) O3 porous carrier.
5. The method for preparing a supported three-way catalyst according to claim 4, characterized in that: The sintering temperature is 1300~1400℃ and the time is 4~6h.
6. The method for preparing a supported three-way catalyst according to claim 2, characterized in that: In S3, the heating temperature is 100~120℃, and the time is 10~14h; the calcination temperature is 900~1100℃, and the time is 2~4h.
7. The method for preparing a supported three-way catalyst according to claim 2, characterized in that: In S4, the concentration of Pt (NO2)2(NH3)2 solution is 1wt%~10wt%.
8. The method for preparing a supported three-way catalyst according to claim 2, characterized in that: In S5, the calcination temperature is 900~1100°C and the time is 2~4h.
9. Use of the supported three-way catalyst according to claim 1 in automobile exhaust treatment.
10. A three-way catalytic converter, characterized in that: The three-way catalyst comprises the supported three-way catalyst according to claim 1.